An Immunohistochemical Study to Assess the Role of Myofibroblasts in Diagnosing and Predicting the Outcome of Oral Squamous Cell Carcinoma - Dr. Priyanka Raghav; Dr. Abhiraj Raghav (International Journal of Cell Biology and Cellular Functions, 2024)
Background: Squamous cell carcinoma (SCC) accounts for approximately 94% of all oral malignancies, hence establishing oral squamous cell carcinoma (OSCC) as one of the top 10 most prevalent malignant tumors. Cells with several functions, such as macrophages and myofibroblasts, play a vital role in the biological behavior of tumors. This study aimed to assess and evaluate the prevalence of myofibroblasts (MF) and macrophages in SCCs occurring in the oral region. Methodology: Samples comprising 15 experimental subjects diagnosed with well-differentiated oral squamous cell carcinoma (WDOSCC), moderately differentiated oral squamous cell carcinoma (MDOSCC), and poorly differentiated oral squamous cell carcinoma (PDOSCC) were included in the study. While 15 healthy subjects were taken as a control group. The tissue samples were divided into sections that were 4 micrometers thick. These sections were subsequently subjected to both conventional staining using hematoxylin and eosin, as well as immunohistochemistry (IHC) staining using α-smooth muscle actin (α-SMA). The comparative analysis of the expression levels of microRNAs was conducted across different stages of OSCC. Statistical analysis was conducted on all the outcomes. Results: The findings revealed that the average final staining index score for patients with WDOSCC was 9.23, while it was 8.98 for those with MDOSCC and 6.54 for individuals with PDOSCC. In contrast, the control group displayed nil MF cellular expressions with statistically significant differences from different grades of OSCC. Conclusion: The present investigation's results indicate that MFs play a significant role in the pathogenesis of OSCCs, and their evaluation may serve as a valuable tool for predicting the invasive characteristics of these malignancies. Therefore, our study suggests the utilization of myofibroblasts (MF) as a stromal marker to aid in identifying invasion and progression in OSCC.
Keywords: Alpha-smooth muscle actin; Oral Cancer; carcinoma; myofibroblast; squamous cell